Stress and Job Satisfaction Among Primary School Teachers after Implementation of the Tri-semester System and Continuous and Comprehensive Evaluation Scheme - Packialakshmi, D.; Anithamary, S. (THE PRIMARY TEACHER, 2018)
The study aims at investigating the stress and job satisfaction among primary school teachers after the implementation of the Tri-semester system and Continuous and Comprehensive Evaluation scheme. The sample consists of 500 primary school teachers in the Kanyakumari District. A self-prepared and standardised Stress Questionnaire and Job Satisfaction Scale were used for data collection. The data was analysed by using mean, standard deviation,‘t’ test and F-test. The present study reveals that the demographic variables such as marital status, type of the family, type of the school, teaching experience, age and monthly income influence the stress of primary school teachers after the implementation of the tri-semester system and continuous and comprehensive evaluation scheme. Also, the present study reveals that the demographic variables such as locality of the school, locality of the house, type of the school, teaching experience, age and monthly income influence the job satisfaction of primary school teachers. There is a significant relationship between stress and job satisfaction of primary school teachers after the implementation of the tri-semester system and the continuous and comprehensive evaluation scheme.